Chronoamperometric investigations of electro-oxidation of lignite in direct carbon bed solid oxide fuel cell. (6th April 2015) - Antunes, Rui; Skrzypkiewicz, Marek
Abstract This paper presents investigations into chronoamperometric experiments performed on solid oxide fuel cell fuelled in batch mode by lignite char. The transient current behaviour resulting from a voltage step change from open circuit voltage (∼1 V) to medium voltages (0.89 V) are recorded and analysed with continuous monitoring of outlet anode gas flow by gas chromatography. In this study, the use of an electrochemical approach for simultaneous determination of diffusion coefficient and chemical constant kinetics from single run experiment was investigated. A fundamental review of the mechanism path in direct carbon bed solid oxide fuel cell and its electrochemistry has been revisited. A mechanistic mode has been proposed and experimentally evaluated. It was found that the reaction mechanism is rate limited by electro-oxidation of CO (anode) and the gas transport is driven mainly by natural convection (anode).